A new and striking odontoglossum (orchidaceae: oncidiinae) from Peru - Dalström, Stig; Pérez Ruíz, Saul (Lankesteriana: International Journal on Orchidology, 2014)
A new species of Odontoglossum with an extraordinary long column and filamentose lip callus is described, illustrated with a photograph and a line drawing, and compared with similar and presumably closely related species, such as O. epidendroides and O. juninense. The new species belongs to the Odontoglossum complex with a flexible lip-base attachment, but differs from all other species in that complex primarily by the elongate base of the column, below the attachment of the strap-like lip-base.